2022
DOI: 10.1128/aac.01125-21
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Channels Mediate Hypoionic Shock-Induced Aminoglycoside Potentiation against Bacterial Persisters by Enhancing Antibiotic Uptake

Abstract: Improving the efficacy of existing antibiotics is a promising strategy for combating antibiotic-resistant/tolerant bacterial pathogens that have become a severe threat to human health. We previously reported that aminoglycoside antibiotics could be dramatically potentiated against stationary-phase Escherichia coli cells under hypoionic shock conditions (i.e., treatment with ion-free solutions), but the underlying molecular mechanism remains unknown. Here we show that mechanosensitive (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…In particular, the concentration of tobramycin in CCCP-treated cells was significantly lower than that without CCCP treatment during the full window of treatment except for the 0.5 h time point. Further, we applied the cell-growth inhibition assay as we recently reported , to measure the level of tobramycin accumulated in E. coli cells. Consistently, we found that tobramycin, as extracted from 3 h or 5 h CCCP treatment E. coli stationary-phase cells, suppressed cell growth in a weaker strength than that without CCCP treatment (blue frame in Figure E,F), similarly to what occurred in exponential-phase cells (red frame in Figure E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the concentration of tobramycin in CCCP-treated cells was significantly lower than that without CCCP treatment during the full window of treatment except for the 0.5 h time point. Further, we applied the cell-growth inhibition assay as we recently reported , to measure the level of tobramycin accumulated in E. coli cells. Consistently, we found that tobramycin, as extracted from 3 h or 5 h CCCP treatment E. coli stationary-phase cells, suppressed cell growth in a weaker strength than that without CCCP treatment (blue frame in Figure E,F), similarly to what occurred in exponential-phase cells (red frame in Figure E).…”
Section: Resultsmentioning
confidence: 99%
“…36,37 We discovered several chemical adjuvants including 5-methylindole and n-butanol, with which 1 min co-treatment enables aminoglycosides to eradicate bacterial persisters and multidrug-resistant pathogens. 15,69 Besides, we also developed physical stresses for aminoglycoside potentiation, including hypoionic shock 27,70,71 and rapid freezing, 26 both of which activate membrane-localized mechanosensitive channels for enhancing antibiotic uptake.…”
Section: Disparate Effects Of Cccp On Antibiotic Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…The discovery and development of new antibiotics, including structurally modified existing antibiotics, has played a dominant role in this war ( Brown & Wright, 2016 ; Lewis, 2020 ). In addition, improving the efficacy of existing antibiotics has also attracted attentions in the recent decade ( Allison, Brynildsen & Collins, 2011 ; Peng et al, 2015 ; Liu et al, 2019 ; Wright, 2016 ; Zhao et al, 2020 ; Lv et al, 2022a ; Lv et al, 2022b ), given that these existing antibiotics have been well documented in their toxicity, pharmacokinetics, administration and mechanism of actions.…”
Section: Introductionmentioning
confidence: 99%